Automated Production Line Monitoring System Using Embedded Rfid - Zulkifli, Che Zalina (2013)
In industrial manufacturing, wireless network can be used in supply-chain, retail stock management, electronic security keys, and theft prevention. Manufacturers require an efficient communication and real time feedback to maximize uptime, improve productivity, and provide cost effective solution advancement. This research proposed automated production line monitoring system using embedded RFID through wireless mesh sensor network (WMSN) platform and smart data processing adopted through web-based monitoring system. Embedded devices in the automated production line monitoring system is capable to work as individual units or work together with multiple terminal links such as in WMSN and provide Machine-to-Machine (M2M) communication solution. The reading range capabilities of the proposed system have been tested in the WMSN platform in real world industrial environment. The results obtained shows that the reading range is able to achieve 123 m with the highest power of +3 dBm in Line-of-Sight (LOS). In data collision evaluation with WMSN platform, the average percentage of data received achieved merely 100%. In multi-hop network, the overall proposed system collection time is about 37% lower than the existing RFID tags. Response time within the same specifications shows that the developed server is faster by 30% compared to the existing database. Hence, this is compatible with the output monitoring system since the input is continuously fed based on the standard time of a certain product. The proposed integrated wireless infrastructures are able to minimize approximately 50% of cost compared to other local vendor with wired solutions. In addition, 75% reduction of downtime in the production line which causes the increase in productivity and yield is recorded due to the effective monitoring.